The yeast eIF3 subunits TIF32/a, NIP1/c, and eIF5 make critical connections with the 40S ribosome in vivo - Valášek, Leoš (Cold Spring Harbor Laboratory Press, 2003)
Initiation factor 3 (eIF3) forms a multifactor complex (MFC) with eIF1, eIF2, and eIF5 that stimulates Met-tRNA(i)(Met) binding to 40S ribosomes and promotes scanning or AUG recognition. We have previously characterized MFC subcomplexes produced in vivo from affinity-tagged eIF3 subunits lacking discrete binding domains for other MFC components. Here we asked whether these subcomplexes can bind to 40S ribosomes in vivo. We found that the N- and C-terminal domains of NIP1/eIF3c, the N- and C-terminal domains of TIF32/eIF3a, and eIF5 have critical functions in 40S binding, with eIF5 and the TIF32-CTD performing redundant functions. The TIF32-CTD interacted in vitro with helices 16–18 of domain I in 18S rRNA, and the TIF32-NTD and NIP1 interacted with 40S protein RPS0A. These results suggest that eIF3 binds to the solvent side of the 40S subunit in a way that provides access to the interface side for the two eIF3 segments (NIP1-NTD and TIF32-CTD) that interact with eIF1, eIF5, and the eIF2/GTP/Met-tRNA(i)(Met) ternary complex.